Full wolf moon [large type] : a novel - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2017)
Traveling to an isolated writers' retreat deep in the Adirondacks, Jeremy Logan, an investigator who specializes in unexplained phenomena, discovers a dead hiker whose wounds suggest an unnatural attack before encountering numerous suspects and a woman scientist struggling with the death of her father.